Prospects and challenges of market entry for Austrian companies in an emerging market: The case of Chile - Stefan Rotter; Vito Bobek; Tatjana Horvat (Naše gospodarstvo / Our Economy, 2020)
Chile is, compared to several other South American countries, geographically and demographically rather limited, but despite that it is the second most important trading and investment partner for Austria in this region. The aim of this paper is to gain firsthand insights into the motivations and perceptions of the entry of Austrian firms into the Chilean market by using an exploratory research approach.Interviews with thirteen qualified and experienced persons were conducted and analyzed, using Mayring's qualitative content analysis. The Chilean market is an attractive opportunity for Austrian firms, as it performs quite well in international business environment rankings. The study results indicate a variety of motivationsfor entering the market, as well as diverse entry mode decisions based on numerous factors, together with a prevailing positive perception of the Chilean business environment. Several results probably cannot be generalized for the entire country, as the capital city is the center of business, and research in other regions of Chile might have different results. Challenges have been identified in the matters of language, distance, time, culture, recruitment, complexity, local partners and the indigenous population. Chile is a highly developed emerging market where doing business faces few obstacles. Therefore, the country represents a very attractive location in South America with great potential for Austrian companies.
Keywords: M16; F14; 330; market entry; internationalization; entry mode; business environment in Chile; emerging markets